2018
DOI: 10.1177/1091581818761653
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Memory Impairment Associated With Decreased Endogenous Estradiol in the Hippocampus of Female Rats

Abstract: It is widely known that not only the gonadal estradiol (E2) but also hippocampal E2 plays an essential role in memory process. However, the role of hippocampal E2-enhanced memory mechanism during aging is largely unknown. The aim of the present study was to investigate the effect of age on E2 concentration, the expression level of its receptors, and key steroidogenic enzymes in hippocampus. We also investigated the effect of microglia activation on E2 synthesis in hippocampal neurons. The results showed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Not only have oestrogens been found to play a role in dopaminergic neurodegeneration in PD, but the hormone has been found to have favourable effects on neuroinflammation, oxidative stress and iron metabolism within the context of PD [41]. Furthermore, sex differences in microglial and astrocytic cells, such as their heightened sensitivity to inflammatory stimuli [42][43][44] and their anatomical distribution [45,46], have been postulated to mediate sex differences in cognition and memory [47,48]. It is worthwhile considering that such results may be reflective of the superior baseline performance of females in cognitive measures than males or may be exacerbated by disease process, though prior research has found that sexspecific progression to cognitive impairment cannot be fully explained by this baseline performance, nor disease duration [31].…”
Section: Discussionmentioning
confidence: 99%
“…Not only have oestrogens been found to play a role in dopaminergic neurodegeneration in PD, but the hormone has been found to have favourable effects on neuroinflammation, oxidative stress and iron metabolism within the context of PD [41]. Furthermore, sex differences in microglial and astrocytic cells, such as their heightened sensitivity to inflammatory stimuli [42][43][44] and their anatomical distribution [45,46], have been postulated to mediate sex differences in cognition and memory [47,48]. It is worthwhile considering that such results may be reflective of the superior baseline performance of females in cognitive measures than males or may be exacerbated by disease process, though prior research has found that sexspecific progression to cognitive impairment cannot be fully explained by this baseline performance, nor disease duration [31].…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that estrogens might protect against memory impairment through the regulation of neurogenic inflammation by inhibiting NF-κB activity [111]. Analogously, the reduction of estradiol level and the expression of its receptors in hippocampus of aged female rat has been shown to contribute to the deficit of spatial memory performance in the Morris water maze test [112]. Nevertheless, a recent paper recommended to carefully consider the positive effect of estrogens on cognition, suggesting that these hormones can enhance and impair learning depending on the mem-ory system [113].…”
Section: Neuroinflammationmentioning
confidence: 98%
“…It has been reported that the decline of E2 is associated with cognitive de cits in female aging rats [6]. A previous study reported that female 18-20-month-old mice and female mice in same age with long-term E2 deprivation all decreased neuronal density in both the arcuate nucleus and preoptic area [50].…”
Section: Discussionmentioning
confidence: 90%
“…Estradiol (E2) is not only synthesized in ovaries but also in nonreproductive tissues, including liver, heart, muscle, bone, and brain that is consistent with a diversity of estrogen actions [5]. It has been reported that the frontal cortical E2 level reduced in female AD patients [2], and the decline of hippocampal E2 is associated with the cognitive de cits in female aging rats [6]. As per these studies, E2 de ciency might facilitate female dementia during aging.…”
Section: Introductionmentioning
confidence: 85%